Determining the role of digital literacy in EFL teaching concerning the views of Turkish EFL Teachers - Ahmed, Kwestan Hussein; Akyıldız, Seçil Tümen (My University, 2022)
The use of digital technologies in English as a foreign language (EFL) teaching has not been addressed enough. Furthermore, the COVID-19 pandemic has emphasized the significance of digital technology and digital literacy in EFL field. This study aims at finding out EFL in-service secondary school (SS) and high school (HS) teachers’ views on the role of digital literacy in their EFL teaching; revealing the level of EFL teachers’ digital literacy and its effects on their teaching, and understanding the facilities of the digital tools and challenges in EFL teachers’ instructions. Further, this study aims to examine the difference between the thoughts of SS teachers and HS teachers about the role of digital literacy in EFL. To achieve these aims, this study utilized a qualitative paradigm to determine the role of digital literacy in EFL classes concerning the views of Turkish EFL teachers, and their perceptions about digital teaching and learning tools in their instruction. First it was found that HS teachers knew the term digital literacy more than the SS teachers. Both SS and HS teachers were confident using digital tools and being digitally literate although some of them could not define the term properly. Secondly digital literacy was claimed to have positive effects on language teaching. Thirdly, all the participants agreed with the fact that the innovations of the digital technologies facilitated their language instruction. Lastly, digital tools had many challenges due to some problems besides their advanteages. All in all, when taken together, the results of this study confirmed the vital role of digital literacy in EFL teaching in the digital age that teachers should acquire and use it actively. Therefore, EFL teachers should incorporate digital literacy in using different digital technologies such as Web 2 tools having several facilities into their instructions. The EFL teachers also admitted the need for trainings and seminars to help them using those tools and become digital natives.
Keywords: Digital Literacy; English as a foreign language teaching (EFL); digital technologies.